Comparison of High and Low Responders to a Cross-Country Skiing Talent Transfer Program: A Coach's Perspective - Stig Arve Sæther; Mats Iversen; Rune Kjøsen Talsnes; Øyvind Sandbakk (MDPI AG, 2021)
Purpose: To examine how coaches differentiate athletes with successful and non-successful development during a cross-country (XC) skiing talent transfer (TT) program. Methods: We conducted qualitative, semi-structured interviews with seven Norwegian coaches working with a group of 23 Chinese summer endurance athletes transferring from running, rowing, and kayaking to the winter endurance sport XC skiing over a six-month training period. The athletes were grouped as either high (n = 9), moderate (n = 3), or low responders (n = 11) based on objective performance development, quantified using laboratory testing. The interview guide contained six sections: physiological development, technical development, psychological characteristics, training and recovery routines, athlete background, and considerations about the effectiveness of TT initiatives in general. Results: The assessments of the coaches revealed that greater development of both physiological and technical capacities among the high-responding TT athletes were associated with higher motivation, as well as superior ability to deal with adversity in the development process. Conclusion: The coaches considered the TT program to be effective; however, successful transfer of athletes to a world class level in a complex sport such as XC skiing requires a multidisciplinary selection process and a longer time frame than the six-month period used in the current project.